THE ROLE OF APPRENTICESHIP JOB TRAINING INSTITUTIONS IN THE COUNTRY ACCORDING TO PERMENAKER NO. 6 OF 2020 IN KARAWANG REGENCY - Abas, Muhamad; Taofik Rohman, Paisal; Rahmatiar, Yuniar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Amid the rapidly evolving economic landscape, challenges in the labor market are becoming increasingly apparent. One major issue faced by many graduates of vocational high schools (SLTA/SMK) and universities is the difficulty in obtaining employment that aligns with their skills and expectations. This study aims to examine the role of Job Training Institutes (LPK) in implementing domestic internship programs in accordance with Minister of Manpower Regulation No. 6 of 2020, with a focus on Karawang Regency. Internships are viewed as a strategic solution to enhance workforce competence and competitiveness while simultaneously reducing unemployment rates. This research employs a qualitative approach designed to understand phenomena within their social context, emphasizing in-depth interaction and communication between the researcher and the subjects studied. The method is structured to collect, analyze, and interpret qualitative data. The findings indicate that internship programs contribute significantly to improving participants' skills, expanding professional networks, and creating employment opportunities. However, implementation challenges remain, including limited human resources, weak regulatory oversight, and the prevalence of illegal brokerage practices. Therefore, strong collaboration among the government, training institutions, and industry stakeholders is essential to building a sustainable and regulation-compliant internship ecosystem.